2021
DOI: 10.1007/s10751-021-01769-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbothermal reduction of mill scales formed on steel billets during continuous casting

Abstract: A billet is a bar made from crude steel which surface contains scales which are rich in iron oxides. This study presents the carbothermal reduction of the scales formed in steel billets. The process included the reaction of the iron oxides contents with carbon (in ratio 5:1) and annealing in a tubular furnace under argon atmosphere. The occurred reactions are discussed using thermodynamic calculations and thermal analysis which indicate a three-stage reduction process Fe3O4 ➔ FeO ➔ Fe3C ➔α-Fe with intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The information provided in the present work would be very useful for posterior attempts to recycle these types of steel slags. As a matter of fact, recently our research group has reported the reduction of the slags produced in SIDERPERU plant [5] and also our initial achievements in recycling them into Q235 steel pieces [6], for which the information provided in the present work were very useful.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The information provided in the present work would be very useful for posterior attempts to recycle these types of steel slags. As a matter of fact, recently our research group has reported the reduction of the slags produced in SIDERPERU plant [5] and also our initial achievements in recycling them into Q235 steel pieces [6], for which the information provided in the present work were very useful.…”
Section: Resultsmentioning
confidence: 77%
“…The partial replacement of cement by steel slags makes a significant contribution to the steel industry and helps to reduce CO 2 emissions [2]. Thus, finding an appropriate use of steel slags is very important for both, to reduce the potential impact on the environment and to maintain the sustainability of natural resources [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As a control, the XRD patterns of Fe‐ZIF‐8 calcined at 850°C and 1050°C were measured (Figure S2). The diffraction patterns of Fe‐NC‐850 contained characteristic peaks of carbon, while the crystallized Fe 2 O 3 (JCPDS: 54‐0489), FeO (JCPDS: 49‐1447), and Fe (JCPDS: 50‐1275) components were detected in Fe‐NC‐1050, showing that the lower pyrolysis temperature was not beneficial to the formation of crystallized iron particles, but the too high temperature complicates the crystallized iron components, due to the inevitable reduction of iron oxides by carbon sources at higher temperatures (1050°C), resulting in various iron species 44,45 . Besides, the XRD pattern of Fe‐AC‐950 (Figure S3) showed the characteristic peaks of Fe and Fe 2 O 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For the recycling, the steel waste should be previously treated in different ways, such as grinding, pressing, bathing, vitrifying, annealing, and other related procedures under various conditions of pressure, atmosphere and temperature [1,6,7]. For example, annealing promotes the oxidation of iron such as hematite (α-Fe 2 O 3 ) and magnetite (Fe 3 O 4 ) and then the iron components can be separated magnetically.…”
Section: Introductionmentioning
confidence: 99%